Stability design of system scaffold with differential settlement. (October 2020) - Chan, Jake L.Y.; Lo, S.H.
Abstract: Differential settlement of system scaffold which is normally ignored in analysis was reported and can lead to premature structural failure. A known collapse case of system scaffold with differential settlement is investigated and presented. Consequently, the use of "permissible limit" or safety factor should not precludes for direct consideration of second-order effect on a structure resulted by differential settlement. A second-order inelastic analysis with an efficient curved quartic function (CQF) element co-developed by the first author is carried out to determine the ultimate load bearing capacity of full-scale system scaffolds in various configurations with support springs under dominant gravity loads. Based on the finding, this study generalizes that the effect of support movement on system scaffold has great influence to its ultimate load bearing capacity. The findings of this research aim to improve the current design practice of large-scale system scaffold by directly considering differential settlement at supports if necessary.